Research on logging: comparison of reduced-impact logging and conventional logging techniques - Kartawinata, K.; Dwiprabowo, H.; Sist, P. (CIFOR and ITTO, 2002)
This chapter provides a brief overview of the reduced impact logging (RIL) as one of the main objectives of the first phase of the Bulungan research project. This activity was conducted in response to a question whether timber harvesting can be compatible with other forest services, values and functions. The main objective of RIL is to reduce soil disturbance, damage to residual trees and maintain future production of timber.